Tunable Alginate-Polyvinyl Alcohol Bioinks for 3D Printing in Cartilage Tissue Engineering - Alexandra Hunter Aitchison; Nicholas B. Allen; Kishen Mitra; Bijan Abar; Conor N. O’Neill; Kian Bagheri; Albert T. Anastasio; Samuel B. Adams (Gels)
This study investigates 3D extrusion bioinks for cartilage tissue engineering by characterizing the physical properties of 3D-printed scaffolds containing varying alginate and polyvinyl alcohol (PVA) concentrations. We systematically investigated the effects of increasing PVA and alginate concentrations on swelling, degradation, and the elastic modulus of printed hydrogels. Swelling decreased significantly with increased PVA concentrations, while degradation rates rose with higher PVA concentrations, underscoring the role of PVA in modulating hydrogel matrix stability. The highest elastic modulus value was achieved with a composite of 5% PVA and 20% alginate, reaching 0.22 MPa, which approaches that of native cartilage. These findings demonstrate that adjusting PVA and alginate concentrations enables the development of bioinks with tailored physical and mechanical properties, supporting their potential use in cartilage tissue engineering and other biomedical applications.